THE POPULAR FRONT IN SPAIN: FROM AN INTERCLASS STRATEGY TO “TAKE THE SKY BY ASSAULT”. ANALYSIS OF CASE IN MURCIA ’S REAR. - González Martínez, Carmen (Revista de Historia Social y de las Mentalidades, 2024)
This article is focused on the history of the Spanish Popular Front from its electoral triumph in February 1936, until its final defeat through two perspectives of analysis: the first one is devoted to the attitude of the Chilean and French Popular Fronts toward the Second Spanish Republic during the Spanish Civil War. In particular, this study shows the effects of the defeat of the Second Republic and the arrival of exiles on French society. The second refers to the overcoming of the Spanish Popular Front as a political strategy between classes because of their failure, the main parties of the Popular Front, the PSOE and PCE, tried to create an unifed party through the liaison committees. This second perspective is based on historical experience analyzed in a republican rear area, the region of Murcia. This research uses the funds of Spanish national archives and specialized historiography in order to illustrate and clarify this complex period.